Radial oscillations of local density of states in carbon nanotubes - FERREIRA, MAURO (My University, 2001)
By performing an analytical study of the electronic structure of metallic carbon nanotubes, we show that the local density of states exhibits well-defined oscillations as a function of the nanotube radius. The periods of such oscillations are obtained from size quantization effects derived from folding up finite graphene sheets into tubular structures. A clear analogy with the de Haas?van Alphen effect in metals is established to explain the origin and features of such oscillations. Results of energy change calculations for impurity-doped carbon nanotubes also show the same type of oscillations.
PUBLISHED
Keywords: Physics